Exploring Digital Nudges in Green Purchase Intentions: The Influence of Green Claims and Social Norms - Ornicha Boonpanya (International Telecommunications Society (ITS), 2024)
With the advancement of information and communications technology (ICT), we are exposed to environmental knowledge from various sources and can witness the impacts of environmental crises in real time. Consequently, the rise of global environmental concerns has led to campaigns and initiatives from both the public and private sectors to address these issues. The question remains: Why are sustainable ways of living still far from being achieved, despite industries' efforts to transition to greener pathways and public sector attempts to promote policies that encourage behavioral changes? While environmental awareness is linked to behavior, translating this knowledge into consistent action at the individual level remains an ongoing challenge. Apart from systematic obstacles such as the lack of supportive infrastructure and economic factors, irrational behaviors and ingrained habits often deter individuals from making sustaible choices. Digital nudging harnesses the power of technology to counteract these barriers by influencing more sustainable decisions with various strategies. Therefore, this study aims to investigate how digital nudges with informational provisions influence green purchase intentions.
Keywords: 330; Digital nudges; Green claims; Social norms; Green purchase intentions; Greenwashing